Mises en lumière et zones d’ombre dans l’ouverture au public de la Petite Ceinture ferroviaire de Paris - Ioana Iosa; Cosme Vallet (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The wide and free access to the Little Railway Belt of Paris, represents nowadays a promise made by the City Hall to set up an innovative development device, more economical and more inclusive, gathering participatory building sites, conventional public and private facilities and calls for projects. Based on empirical and immersion work within one of the three mandated skills groups for the implementation of participatory projects from 2016 to 2019, this paper will explore an experimental process : the evolution of the Little Belt and the debate around it, and the process put in place by the City Hall around this project. Through an analysis of discourses and actions of the various actors involved (in particular the experiments put in place by the skills groups), we wish to facilitate the reader’s critical analysis of the balance between urban manufacturing methods (close to marketing), and the freedom left to the inhabitants of Paris, Ile de France and Belt residents in the transformation of this collective wealth. This analysis will allow us to apprehend the spoken and the unspoken, the visible and the invisible — whether it is about stakes and ambitions, or users and uses to stimulate or prevent — to better understand the reasons and effects of the process, as well as the cohabitation between valuation and profitability on the one hand and self-managed urban and citizen projects on the other hand.